2011
DOI: 10.1143/apex.4.065001
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Change in Shape of Platinum Nanoparticles Supported on CeO2during Catalytic Reactions

Abstract: The temperature dependence of the shape of Pt nanoparticles supported on CeO2 for CO oxidation was investigated using environmental transmission electron microscopy. Pt nanoparticles in CO/air become round at room temperature (when catalytic activity is low), while they become partially faceted at elevated temperature (when the catalytic activity is high). Based on a comparison between the shapes of the Pt nanoparticles in vacuum, N2, O2, CO, and CO/air at room temperature, 100, and 200 °C, we propose that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 23 publications
(29 reference statements)
4
51
0
Order By: Relevance
“…However, only a limited amount of atomic-scale information is available about catalytic reactions on the surface of Pt nanoparticles. In the Pt/CeO 2 catalyst specimen that we examined, the conversion of CO to CO 2 was about 10% at room temperature and reached 100% at above 50°C [79].…”
Section: Pt Nanoparticulate Catalystsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, only a limited amount of atomic-scale information is available about catalytic reactions on the surface of Pt nanoparticles. In the Pt/CeO 2 catalyst specimen that we examined, the conversion of CO to CO 2 was about 10% at room temperature and reached 100% at above 50°C [79].…”
Section: Pt Nanoparticulate Catalystsmentioning
confidence: 92%
“…Through quantitative analysis [79], we found that the shape of the Pt nanoparticles changes depending on temperatures. At a low catalytic activity state, particles appeared to be round, while at a high activity state they were partially facetted.…”
Section: Correlation Of the Catalytic Activity With The Morphology Ofmentioning
confidence: 99%
“…A detailed characterization of the nanoparticle surface and the site-specific reactivity is therefore required to describe the catalytic performance of nanoparticles. However, nanoparticles often respond dynamically to changes in the surrounding environment, because changes in the gas composition affect the free energy of the exposed surfaces [2][3][4][5] . The surface structure and reactivity are therefore coupled to the reaction conditions, emphasizing the need for identification of active sites and their properties in situ, during catalysis.…”
mentioning
confidence: 99%
“…We have observed Pt/CeO 2 catalysts that are currently used as a component in three-way catalysts for automobile exhaust gas treatment and it shows catalytic activity for CO oxidation. Our systematic ETEM observations have correlated the morphology of Pt nanoparticles in various gases to the enormous amount of information available about the surface structure of bulk metals [5].…”
Section: B In-situ Observations Of Supported Nanoparticle Catalysts mentioning
confidence: 99%
“…The ETEM of this type can provide us sufficient room around a sample for the variety of high-resolution in-situ observations [1,2]. Some recent applications of ETEM by our research group are briefly compiled in this presentation including the growth of carbon nanotubes (CNTs) [3,4] and the catalytic activity of supported metal nanoparticles [5].…”
Section: Introductionmentioning
confidence: 99%